Pengaruh Kompetensi Sumber Daya Manusia, Sistem Akuntansi Keuangan Daerah (SAKD) dan Sistem Pengendalian Intern Terhadap Kualitas Laporan Keuangan - Dewi, I Gusti Ayu Krisna; Marvilianti Dewi, Putu Eka Dianita (Jurnal Akuntansi Profesi, 2020)
This Study aims to determine the effect of human resource competence, regional financial accounting systems (SAKD), and internal control systems on the quality of the financial statements of the provincial government of Bali (empirical study on the SKPD of the Province of Bali). The type of research is quantitative research. The sampling technique in this study used a purposive sampling method. Using a sample of 156 taxpayers. The data collection technique was questionnaire. The data analysis used multiple linear regression with the help of SPSS 20.The results of the study show that: (1) human resource competence has a positive effect on the quality of the financial statements of the provincial government of Bali; (2) the regional financial accounting system (SAKD) has a positive effect on the quality of the financial statements of the provincial government of Bali; and (3) internal control system has a positive effect on the quality of the financial statements of the provincial government of Bali.